Corrigendum to: Kearifan Ritual Jodangan dalam Tradisi Islam Nusantara di Goa Cerme [15(1), (2017), 42-57] - Editorial IBDA (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
Corrigendum to: Takdir, Muhammad, (2017), IBDA, [15(1), (2017), 42-58] doi: 10.24090/ibda.v15i1.2017.pp42-58, in the article, author name typed as "Mohammad Takdir Ilahi". Last name deleted, so the author's full name is "Mohammad Takdir".